The self in Husserl's phenomenology - Herrera Restrepo, Daniel (Estudios de Filosofía, 1999)
Although in the works of Husserl there are references to a self as body, a self as person and a trascendental self, this entity living in our body as if the latter were its container does not exist. Husserl rejects a dualistic conception of man. For him, a human is a dynamically, intentionally, and teleologically structured whole, who can experience the world in a meaningful way. No other statement defines better the being of men, and its meaning, than the "lije that experiences the world"